PROGRAM KEMITRAAN BAGI KADER LANSIA MELALUI SENAM OTAK DALAM PENCEGAHAN DEMENSIA DI WILAYAH KERJA PUSKESMAS TRENGGALEK - Rahayu Niningasih; Dewi Wulandari; Ixora Ixora (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
Trenggalek Community Health Center is an innovative care center that provide a service to the elder people. However, until now there is no check-up or examination about Dementia to the elder people. One of the alternatives to prevent the case of Dementia is brain gym. The purpose of community service was to provide additional knowledge about Dementia and brain gym to prevent Dementia. The method of this community service was providing education, measuring the community knowledge about Dementia and performing brain gym. The result of community service showed that there was a significant improvement of knowledge before and after education. The brain gym was performed by the participants of elder people community. The attendance of participants was 100% and they were very enthusiastic in performing brain gym.